Sexual Dimorphism of Index (2D) and Ring (4D) Digit Lengths and Their Ratio (2D:4D) Among Adult Bangladeshi Male (Bangladesh Journal of Anatomy, 2015)
Context: Human hand is one of the most studied subjects in modern science and evolutionary biology. By virtue of evolution and genetically arrangements, digital lengths vary from person to person according to age, sex, races, occupation or even environmental influences. It has been found that the digital lengths and their ratios are not the same in different sexes or even both hands. Specially, index to ring digit lengths and their ratios which already have been proved to represent sexual dimorphism may differ in both hands of an individual. Many studies among different races have shown that index to ring digit ratio (2D:4D)  31 among female and